Pemeriksaan Os Cruris dengan Proyeksi Modifikasi Arah Sinar Horizontal pada Kasus Fraktur - Kus Endah Aryati; Sri Sugiarti (Poltekkes Kemenkes Semarang, 2021)
Background: Os cruris examination technique with modification projections is usually done in patients with fracture cases.Methods: This study aims to determine the results of the positioning, examination techniques, and radiograph results of the os cruris examination technique with projected modifications in fracture cases. The design of this research is descriptive research with a case study approach. In the case of research fractures using 4 samples and data collection by observation, checklist, documentation, and interviews.Results: the os cruris examination technique with projected modification in fracture cases can already diagnose well but does not produce true lateral radiographs.Conclusions: Projection modification is done if there is a fracture in the os cruris area in a non-cooperative patient so that it can provide more optimal radiographic results and the patient will be more comfortable when positioned.